Illusions - Pike, Aprilynne (HarperTeen, 2012)
As her senior year of high school starts, Laurel is just beginning to adjust to Tamani's absence when he suddenly reappears, telling her he must guard her against the returning threat of the trolls that pose a danger both to her and to Avalon.